A Comprehensive Literature Review of Antithrombotic Treatment for Cervical Artery Dissection - Andina, Andina; Indra Hadi, Indra Hadi; Muhammad Rezky, Muhammad Rezky (International Medical Journal Corp. Ltd, 2024)
Background: The literature on antithrombotic treatment for cervical artery dissection (CAD) reveals a complex interplay of therapeutic strategies, clinical outcomes, and ongoing debates regarding the optimal management of this condition. The foundational work by (E Hinson et al., 2010) underscores the critical need for systematic evaluation of antithrombotic therapy in trauma patients with CAD, highlighting the potential risks and benefits associated with anticoagulants and antiplatelet agents. This initial exploration sets the stage for subsequent studies that delve deeper into the comparative efficacy of these treatment modalities. Literature Review: The article discusses the relationship between physical trauma, particularly neck movements involving hyperextension and rotation, and the onset of CAD. This correlation is critical for clinicians to consider when assessing patients with a history of neck trauma, as it may inform both diagnosis and treatment strategies. The authors’ assertion that the prognosis for disability following CAD is generally favorable, with a low mortality rate, provides a reassuring perspective for both clinicians and patients. Conclusion: In conclusion, the literature on antithrombotic treatment for cervical artery dissection illustrates a pressing need for further research to clarify the optimal management strategies. The existing studies highlight the complexities surrounding treatment efficacy, the necessity for standardized guidelines, and the importance of a comprehensive understanding of CAD's clinical implications. The call for larger, multicenter studies is vital to address the current gaps in knowledge and improve patient outcomes in this challenging area of clinical practice.